Не вся La vie: [рассказы] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2012)
Экземпляры: ЦБ (20170313) / Инвентарный номер: 53593 / Цена: 60.00 / Сис.шифр: Р2 / Авт.знак: Т 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6